(3JCLjQ GSJZdGd GdWGFQGJ (B/ s - (3eMeO ahRj YHOGdHGbj s; (3SejMI eUWaj GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JYQVfG ai gPg GdQSGdI dehVhY JCLjQ GSJZdGd GdWGFQGJ hPdc dGYJeGO cGaI TQcGJ GdWjQGf Ydi eSJhj GdYGde Ydi gPg GdhSjdI ai JLgjR CSGWjdgG ef GdWGFQGJ hGdeYOGJ GddGReI dJTZjd GdWGFQGJ(B. (3hHOCfG gPg GdQSGdI HaUd JegjOj jJfGhd JYQja GdWGFQI hGdCYeGd GdbGfhfjI GdJi JQO YdjgG , Ke JfGhdfG ai HGHjf eJJGdjjf UhQ JCLjQ GSJZdGd GdWGFQGJ ShGA cGf JCLjQ GSJZdGd GdWGFQI eLgRI Ch ZjQ eLgRI (B: (3hJCUjd eSFhdjI eDLQ h ef JYhjV GdCVQGQ hOhQ GdJCejf GdLhj ai Pdc s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2015s
(3HHdjhLQGajG(B: (3UaMGJ (B221-231s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3JCLjQ GdWGFQI eLgRI s; (3JMGdaGJ GdWjQGf GdYGdejIs; (3GdMLR Ydi GdWGjQI hHjYgG LHQkGs; (3TgGOGJ GdUdGMjI ddWjQGfs; (3JCLjQ GSJZdGd GdWGFQGJ eLgRI hZjQ eLgRIs; (3GJaGbGJ GdJfSjb hGdJYGhf GdLhjs; (3eSFhdjI eSJZd GdWGFQIs; (3GTJQGWGJ GdMUhd Ydj TgGOI QNUI GdeSJKeQ GdLhis; (3GdTGQJQs; (3Qgf GdWGFQIs; (3GdJCejf GdLhj s